Bitcoin, LQ45 Index, Mutual Fund NAV, and Mining NPM Impact on Gold as Safe Haven - Rafael Ivo Jonatan; Rendra Arief Hidayat (International Forum of Researchers and Lecturers, 2025)
This study analyzes the effect of Bitcoin prices, the LQ45 Index, mutual fund net asset value (NAV), and the net profit margin (NPM) of gold mining companies on the price of gold as a safe haven asset within the context of the Indonesian financial market. Gold is often seen as a safe haven asset that is the primary choice of investors when economic uncertainty increases, but the relationship between gold and various other investment instruments still requires further study. This study uses a multiple linear regression method with a robust standard errors approach to analyze 420 monthly and quarterly data observations during the 2018-2022 period. The results of the study found that the price of Bitcoin and the NPM of gold mining companies had a significant positive influence on the price of gold, while the LQ45 Index had a significant influence effect. Meanwhile, the NAV of mutual funds showed a significant positive influence that was not in line with the initial hypothesis. These findings indicate that gold does not always function absolutely as a safe haven asset, as its role is contextual and still influenced by the dynamics of other investment instruments such as digital assets, stock markets, and mutual funds. The study's results make an important contribution to financial literature by proving that the safe haven characteristics of gold are complex and dynamic, so investors need to consider various factors and market conditions before allocating investments to gold as a hedging strategy in their portfolios.